Assessing the perception of stakeholders regarding the impact of coastal tourism on the environment in the Romanian Black Sea coastal area - Stan, Mari-Isabella; Aivaz, Kamer-Ainur; Vintil?, Drago?-Florian; Ioni?iu, Ionela (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The coastal and marine area is one of an endlessly increasing number of human activities and provisions, the most significant of which are those associated with tourism. With the start of the MARSPLAN BS-II project in 2019, the planning of public participation actions of stakeholders to identify areas and important features for each maritime activity to develop and implement MSP has started. This study, using an appropriate exploratory approach, namely Grounded Theory, aims to assess stakeholders' perceptions of the environmental impact of tourism in the Romanian Black Sea coastal area to identify potential barriers that may arise from the perspective of implementing the Black Sea MSP. Even if the impact of tourism on the environment cannot be studied in-depth and fully proven, it is obvious, through our results, that tourism should fully enjoy the management and planning efforts.